2021
DOI: 10.25048/tudod.910260
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sodium Glucose Co-Transporter 2 Inhibitor (SGLT2i) in Geriatric Population

Abstract: Aim: Diabetes treatment and follow-up is more difficult and sensitive in the elderly. Sodium glucose co-transporter type 2 (SGLT2) inhibitors are newly developed antidiabetic agents. In the geriatric age group, the use of SGLT2 inhibitors may be riskier in terms of side effects. We planned to evaluate the effect and tolerability of using SGLT2 inhibitors in geriatric patients. Material and Methods:Patients over 65 years of age with a diagnosis of type 2 DM who were started on empagliflozin or dapagliflozin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Studies have also shown that SGLT2 inhibitors increase hemoglobin and hematocrit values (13,14). Dapagliflozin has been shown to exert this effect by increasing hepcidin levels (15), while empagliflozin has been shown to increase erythropoiesis and increase hemoglobin and hematocrit values (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that SGLT2 inhibitors increase hemoglobin and hematocrit values (13,14). Dapagliflozin has been shown to exert this effect by increasing hepcidin levels (15), while empagliflozin has been shown to increase erythropoiesis and increase hemoglobin and hematocrit values (16).…”
Section: Discussionmentioning
confidence: 99%
“…Total cholesterol was measured by enzymatic colorimetric method and highdensity lipoprotein cholesterol was measured by enzymatic colorimetric method with a Hitachi modular autoanalyzer (Roche Diagnostic Corp., Indianapolis, IN, USA). Lowdensity lipoprotein cholesterol level was calculated with the Friedewald formula for patients with triglyceride levels of <400 mg/dL (14). Patients with triglyceride of >400 mg/ dL were evaluated by enzymatic colorimetric method with the second-generation LDL-C Plus Kit and the Hitachi Modular P800 (Roche Diagnostic Corp., Indianapolis, IN, USA).…”
Section: Laboratory Parametersmentioning
confidence: 99%